The Impact of Earthquake on Small Business Performance: Evidence from Small Accommodation Services in Ranau, Sabah - Noor Fzlinda Fabeil; Kamarul Mizal Marzuki; Izyanti Awang Razli c; Mohd Rizwan Abd Majid d ,; Marry Tracy anak Pawan (2018)
The earthquake which occurred on the 5th of June 2015 in Ranau, Sabah was considered to be the most devastating incident not only to the residents but also to local small businesses in the district. The aftermath caused tragic deaths of 18 people on Mount Kinabalu, physical damages of buildings, and lifeline disruptions as well as day-to-day business activities, including the hotels and resthouses. Numerous studies have been focusing on the damage assessment and risk quantification of natural disaster aftershock, but there is a lack of studies on the impact of earthquake on small business performance in terms of physical and emotional aspects before, during and after disaster. Much is still unknown the actual condition of small accommodation businesses in Ranau due to earthquake, especially in terms of operation status and recovery strategy to survive in their business. Therefore, this study aims to explore from the perspectives of manager of accommodation services in Ranau, Sabah about their business performance and strategy before, during and after the earthquake. A structured face-to-face interview was conducted with 33 managers of hotels, resorts and homestays in Ranau, which the list were drawn from the Sabah Tourism Board. The analysis of data revealed that the earthquake caused severe impact on their business performance in terms of operation, physical and emotional aspects. In addition, internal recovery strategies were more preferable than the external support for their business recovery. It International Academic Journal of Business Management, is hoped that this study may provide valuable insights to small tourism-related business and related agency to develop effective measures to prepare and support the business before or after natural disaster.